Cross-Talk Between the Intestinal Epithelium and Salmonella Typhimurium - Ménard, Sandrine; Lacroix-Lamandé, Sonia; Ehrhardt, Katrin; Yan, Jin; Grassl, Guntram A.; Wiedemann, Agnès (Frontiers in Microbiology, 2022)
Salmonella enterica serovars are invasive Gram-negative bacteria, causing a wide range of diseases from gastroenteritis to typhoid fever, representing a public health threat around the world. Salmonella gains access to the intestinal lumen after oral ingestion of contaminated food or water. The crucial initial step to establish infection is the intestinal epithelial passage. Human-adapted serovars such as S. Typhi or S. Paratyphi disseminate to systemic organs and induce life-threatening disease known as typhoid fever, whereas broad-host serovars such as S. Typhimurium usually are limited to the intestine and responsible for gastroenteritis in humans. To overcome this epithelial barrier, Salmonella developed mechanisms to induce cellular invasion, intracellular replication and to face host defence mechanisms. Depending on the serovar and the respective host organism, disease symptoms differ and are linked to the ability of the bacteria to manipulate the epithelial barrier for its own profit and cross the intestinal epithelium. To better understand S. Typhimurium pathogenesis, it is crucial to characterize the crosstalk between S. Typhimurium and the intestinal epithelium and decipher the mechanisms and epithelial cell types involved. Thus, the purpose of this review is to summarize our current knowledge on the molecular dialogue between S. Typhimurium and the various cell types constituting the intestinal epithelium with a focus on the mechanisms developed by Salmonella to cross the intestinal epithelium and get access to subepithelial or systemic sites and survive host defense mechanisms.